Politeness Strategies Used by the Member of Student Youth Community (SYC) Widya Gama Mahakam University - Febiyani Febiyani; Rinda Fitriana; arbain arbain (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2019)
Politeness strategy is a strategy that used by the people in order to safe and satisfy the hearers’ face. This strategy mainly used in everyday communication and interaction. This research used qualitative resarch and aimed to find what are politeness strategies used by the member of Student Youth Community (SYC). This research conducted in Widya Gama University with 15 members of SYC who involved as the research subject. The result of this research showed that there are four strategies used by the Members of SYC. They are bald on record, positive politeness strategy, negative politeness strategy, and off record strategy. From 277 utterances, 116 utterances of them recognized as bald on record (42%), 110 utterances as positive politeness (40%), 18 utterances as negative politeness (6%), and 33 utterances as off record (12%). Therefore, it can be concluded that bald on record as the dominated strategy that used by the members of SYC. It means that, during the discussion and interaction, the members of SYC tend to use direct srategy.